The effect of acute caffeine ingestion on coincidence anticipation timing in younger and older adults. (September 2014) - Duncan, Michael J.; Tallis, Jason; Wright, Sheila Leddington; Eyre, Emma L. J.; Bryant, Elizabeth; Langdon, Dominic
<x content-type="archive" xml:space="preserve">Abstract</x> Objectives This study compared the effect of acute caffeine ingestion on coincidence timing accuracy in younger and older adults. Methods Thirteen young (aged 18–25 years, age: 20 ± 2 years, 7 females, 5 males) and 13 older (aged 61–77 years, age: 68 ± 6 years, 9 females, 3 males) adults, all who were habitual moderate caffeine consumers undertook measures of coincident anticipation timing performance pre- and post-acute caffeine (3 mg/kg) or placebo ingestion administered in a double blind, randomized fashion. Results Results indicated significant pre-to-post X substance (caffeine vs. placebo) interactions for absolute (P = 0.02, Pη2 = 0.204) and variable error (P = 0.015, Pη2 = 0.221). In both cases, error (absolute or variable) improved pre-to-post ingestion in the caffeine condition but not in the placebo condition. There were no significant differences due to age (younger vs. older adults, P > 0.05) in any of the analyses. Discussion The results of this study suggest that acute caffeine ingestion positively influence coincidence anticipation timing performance in both younger and older adults, who are moderate habitual caffeine consumers. Such effects might therefore be useful for older adults in enhancing ability to undertake cognitive-perceptual tasks which involve interceptive actions.